CHIP Decline Is Associated With Isoflurane-Induced Neurodegeneration in Aged Mice - Xu, Qiaoqiao; Xiong, Juan; Xu, Li; Wu, Yuanyuan; Li, Man; Li, Qinqin; Jiang, Tao; Luo, Ailin; Zhang, Yi (Frontiers in Neuroscience, 2022)
Perioperative neurocognitive disorders (PND) commonly occur in the elderly patients, and isoflurane could be a risk factor. During the pathogenesis of neurodegeneration, ubiquitin proteasome system (UPS) is participated in the process of aging, which affects the synaptic plasticity and synaptic function. However, whether UPS is involved in the etiology of PND is unclear. In this study, we examined the expression change of ubiquitin E3 ligase protein heat shock cognate 70 (HSC70)-interacting protein (CHIP) and the function turbulence of UPS in isoflurane exposed aged mouse, to illustrate the role of UPS in PND. The neurodegenerative behavioral changes were shown in isoflurane exposed aged mice, correlated with neuropathological changes manifested with reduced number of intersections and spine density in the cortex. Ubiquitin function was decreased while the apoptosis was activated, and CHIP protein expression decline altered synapsin expression and phosphorylation associated with the neurodegeneration in isoflurane induced PND. Aging was the big important factor. And it remained consistent was the synapsin phosphorylation/dephosphorylation level changes in CHIP knock-down N2a cells. Our observation the decline of CHIP protein expression and synaptic degeneration might reveal the reason for synaptic degeneration in the underlying pathogenesis of PND caused by isoflurane.